Milne Fiord CTD (Conductivity, Temperature, Depth) profiles ... - Mueller, Derek; Bonneau, Jérémie; Hamilton, Andrew; Antropova, Yulia; Forrest, Alex; Lavel, Bernard (Canadian Cryospheric Information Network, 2024)
Conductivity, Temperature, Depth (CTD) profiles taken in Milne Fiord during summer (July) fieldwork campaigns. Profiles were collected primarily using an RBR XR620 CTD, but also with an RBR Concerto and an Idronaut Ocean Seven 304Plus during some campaigns. The CTD was deployed at sites accessed by foot, snowmobile, and helicopter through augered holes in the sea ice or epishelf lake ice or through natural leads or fractures in the Milne Ice Shelf or Milne Glacier tongue, as well as through leads in the sea ice offshore. The CTD was lowered on a 2.5 mm synthetic line using a hand reel to a nominal depth of 15 m for 2 minutes to equilibrate, raised to the surface, and then lowered at 0.5-1.0 m/s to the bottom, then raised at 1-2 m/s to the surface. Raw data were processed in MATLAB based on steps outlined in the Seabird Data Processing Manual (Seabird Scientific, 2017) and Halverson et al. (2017). Processing steps included an atmospheric pressure correction based on in-air pressure readings, low-pass ... : CTD profiles were conducted to examine the oceanography of Milne Fiord from the glacier grounding line to the open ocean. These observations were collected to examine variability in water properties along and across the fiord, to infer the position and height of topographic sills, to look for deep water renewal events and to examine the amount of melt water from the glacier, ice shelf or watershed. ...